Question
upstudy study bank question image url

8) \( \frac{1+11}{4}-\frac{11}{7}+8 \leq 11+3 \)

Ask by Gross Bryant. in Kazakhstan
Feb 14,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\(\frac{66}{7} \leq 14\)

Solution

Calculate the value by following steps: - step0: Calculate: \(\frac{\left(1+11\right)}{4}-\frac{11}{7}+8-\left(11+3\right)\) - step1: Remove the parentheses: \(\frac{1+11}{4}-\frac{11}{7}+8-\left(11+3\right)\) - step2: Add the numbers: \(\frac{1+11}{4}-\frac{11}{7}+8-14\) - step3: Add the numbers: \(\frac{12}{4}-\frac{11}{7}+8-14\) - step4: Divide the terms: \(3-\frac{11}{7}+8-14\) - step5: Calculate: \(-3-\frac{11}{7}\) - step6: Reduce fractions to a common denominator: \(-\frac{3\times 7}{7}-\frac{11}{7}\) - step7: Transform the expression: \(\frac{-3\times 7-11}{7}\) - step8: Multiply the numbers: \(\frac{-21-11}{7}\) - step9: Subtract the numbers: \(\frac{-32}{7}\) - step10: Rewrite the fraction: \(-\frac{32}{7}\) Let's solve the inequality step by step. 1. **Calculate the left side of the inequality:** \[ \frac{1 + 11}{4} - \frac{11}{7} + 8 \] - First, calculate \(1 + 11 = 12\). - Then, \(\frac{12}{4} = 3\). - Now, we have: \[ 3 - \frac{11}{7} + 8 \] - Next, convert \(3\) and \(8\) to have a common denominator with \(\frac{11}{7}\): \[ 3 = \frac{21}{7} \quad \text{and} \quad 8 = \frac{56}{7} \] - Now, combine these: \[ \frac{21}{7} - \frac{11}{7} + \frac{56}{7} = \frac{21 - 11 + 56}{7} = \frac{66}{7} \] 2. **Calculate the right side of the inequality:** \[ 11 + 3 = 14 \] 3. **Set up the inequality:** \[ \frac{66}{7} \leq 14 \] 4. **Convert \(14\) to a fraction with a denominator of \(7\):** \[ 14 = \frac{98}{7} \] 5. **Now, compare the two fractions:** \[ \frac{66}{7} \leq \frac{98}{7} \] This inequality is true since \(66 \leq 98\). Thus, the final result is: \[ \frac{66}{7} \leq 14 \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

Let's break down the expression on the left-hand side first. We start with \( \frac{1+11}{4} - \frac{11}{7} + 8 \). Calculating \( \frac{1+11}{4} = \frac{12}{4} = 3 \). Now we have \( 3 - \frac{11}{7} + 8 \). Next, we can convert \( 3 \) and \( 8 \) into fractions with a common denominator (let's use 7): \( 3 = \frac{21}{7} \) and \( 8 = \frac{56}{7} \). So, combining these: \[ \frac{21}{7} - \frac{11}{7} + \frac{56}{7} = \frac{21 - 11 + 56}{7} = \frac{66}{7}. \] Now, let's evaluate the right-hand side: \( 11 + 3 = 14 \). Now we want to see if \( \frac{66}{7} \leq 14 \). To compare, we can express 14 in terms of the denominator 7: \( 14 = \frac{98}{7} \). Now, we compare: \[ \frac{66}{7} \leq \frac{98}{7}. \] Since 66 is less than 98, we can conclude: \( \frac{66}{7} \leq 14 \), so the inequality holds true. Thus, the original inequality is satisfied.

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy